Propozycja miary efektywności innowacyjności w hierarchicznym przekroju regionalnym z wykorzystaniem European Innovation Scoreboard - Strahl, Danuta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents the proposal of the measurement of regional innovation effectiveness. The proposal is based on the tools of multidimensional statistical analysis as well as on the European Innovation Scoreboard. The measure of innovation effectiveness is presented in a regional dimension following two concepts: as the measure referring to a region and as the measure related to a hierarchical system in a regional cross-section that is e.g. to a country in its regional cross-section. Such a measure allows one to consider interregional diversification in a specific country and define the influence of such diversification on the system innovation. Innovation effectiveness is referred to as the relation between regional innovation indices INPUT and OUTPUT type, taking into consideration classification of regions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (19); 2007; nr 1180, s. 9-18